Combined Treatment With Pembrolizumab and Allogenic BK Virus-Specific T Cells in Progressive Multifocal Leukoencephalopathy: A Case Report. Issue 5 (September 2021) - Wicklein, Rebecca; Heidegger, Simon; Verbeek, Mareike; Eiz-Vesper, Britta; Maecker-Kolhoff, Britta; Kirschke, Jan Stefan; Page, Agata; Korn, Thomas; Hemmer, Bernhard; Deschauer, Marcus
Abstract : Objective: We report a combination of BK virus-specific T cells and pembrolizumab as a treatment option in progressive multifocal leukoencephalopathy (PML). Results: A 57-year-old male patient diagnosed with PML presented a fast-progressing right hemiparesis, aphasia, and cognitive deficits. Brain MRI showed a severe leukoencephalopathy with diffusion restriction. The patient was treated with 10 doses of pembrolizumab (2 mg/kg body weight) in differing intervals and 2 partially human leukocyte antigen-matched allogenic BK virus-specific T cell transfusions after the fifth pembrolizumab treatment. Although pembrolizumab alone decreased the viral load but failed to control the virus, BK-specific T cell transfer further enhanced the decline of JC virus copies in the CSF. Moreover, the regression of leukoencephalopathy and disappearance of diffusion restriction in subsequent brain MRI were observed. The combined treatment resulted in a clinical stabilization with improvements of the cognitive and speech deficits. Discussion: This case supports the hypothesis that pembrolizumab is more efficient in the presence of an appropriate number of functional antigen-specific T cells. Thus, the combined treatment of pembrolizumab and virus-specific T cells should be further evaluated as a treatment option for PML in future clinical trials.